'PARP'ing fibrosis: repurposing poly (ADP ribose) polymerase (PARP) inhibitors. Issue 7 (July 2020) - Rao, Pooja Dhileepkumar; Sankrityayan, Himanshu; Srivastava, Anjali; Kulkarni, Yogesh A.; Mulay, Shrikant R.; Gaikwad, Anil Bhanudas
Highlights: Understanding different pathways leading to PARP activation. Role of PARP in the pathogenesis of lung, heart, liver and kidney fibrosis. PARP inhibitors as a possible repurposing candidate. Therapeutic potential of PARP inhibitors to combat organ fibrosis. Abstract : Fibrosis is a wound-healing process that results in tissue scarring and organ dysfunction. Several novel mechanisms of fibrogenesis have been discovered recently. In this review, we focus on the role of poly-ADP ribose polymerase (PARP) in major organ fibrosis, such as lungs, heart, liver, and kidneys. PARP is a dynamic enzyme that modulates different cellular proteins by the addition of PAR groups and mediates an array of cellular events in both normal physiological and pathophysiological states. The US Food and Drug Administration (FDA) and European Medicines Agency (EMA) recently approved several PARP inhibitors, such as olaparib, niraparib, talazoparib, and rucaparib, for the treatment of ovarian and germline BRCA-mutant breast cancers. Consequently, repurposing these drugs could provide an opportunity to counter organ fibrosis.